Voxel‐based magnetic resonance image postprocessing in epilepsy. (26th July 2017) - Martin, Pascal; Winston, Gavin P.; Bartlett, Philippa; de Tisi, Jane; Duncan, John S.; Focke, Niels K.
Summary: Objective: Although the general utility of voxel‐based processing of structural magnetic resonance imaging (MRI) data for detecting occult lesions in focal epilepsy is established, many differences exist among studies, and it is unclear which processing method is preferable. The aim of this study was to compare the ability of commonly used methods to detect epileptogenic lesions in magnetic resonance MRI‐positive and MRI‐negative patients, and to estimate their diagnostic yield. Methods: We identified 144 presurgical focal epilepsy patients, 15 of whom had a histopathologically proven and MRI‐visible focal cortical dysplasia; 129 patients were MRI negative with a clinical hypothesis of seizure origin, 27 of whom had resections. We applied four types of voxel‐based morphometry (VBM), three based on T1 images (gray matter volume, gray matter concentration, junction map [JM]) and one based on normalized fluid‐attenuated inversion recovery (nFSI). Specificity was derived from analysis of 50 healthy controls. Results: The four maps had different sensitivity and specificity profiles. All maps showed detection rates for focal cortical dysplasia patients (MRI positive and negative) of >30% at a strict threshold of p < 0.05 (family‐wise error) and >60% with a liberal threshold of p < 0.0001 (uncorrected), except for gray matter volume (14% and 27% detection rate). All maps except nFSI showed poor specificity, with high rates of false‐positive findings in controls. In the MRI‐negative patients, absolute detection rates were lower. A concordant nFSI finding had a significant positive odds ratio of 7.33 for a favorable postsurgical outcome in the MRI‐negative group. Spatial colocalization of JM and nFSI was rare, yet showed good specificity throughout the thresholds. Significance: All VBM variants had specific diagnostic properties that need to be considered for an adequate interpretation of the results. Overall, structural postprocessing can be a useful tool in presurgical diagnostics, but the low specificity of some maps has to be taken into consideration.